Revisiting the guidelines and choice the ideal substitute for aortic valve endocarditis - Nappi, Francesco (Ann Transl Med, 2020)
Aortic valve replacement is the most commonly performed cardiac surgical operation worldwide for infective endocarditis (IE). Long-term durability and avoidance of infection relapse are the treatment goals. However, no detailed guidelines on prosthesis selection and surgical strategy are available. Management should be guided by a comprehensive evaluation of infection extension and its microbiological characteristics, the clinical profile of the patient and the risk of infection recurrence. We conducted a literature search of the PubMed database, EMBASE and Cochrane Library (through November 2019) for studies reporting to the use of biological substitutes in aortic valve endocarditis (AVE). Studies comparing long-term outcomes in the use of allogenic and autologous with conventional prostheses were investigated. Conventional mechanical or stented xenografts are the preferred choice for localized aortic infection. In cases of complex IE with the involvement of the root or the aorto-mitral continuity, the use of homografts are recommended, according to surgeon’s and center experience. Homograft use needs to be balanced against the risk of structural degeneration. Prosthetic bioroot or prosthetic valved conduit with a mechanical or bioprosthetic valve are acceptable alternatives. The choice of aortic valves substitute and surgical strategy in IE is multifaceted. Principles guiding the selection of prosthesis and surgical approach rely on the long-term durability and the avoidance of infection relapse. A decisional algorithm considering the extension of the infection and its microbiological characteristics, the clinical profile of the patient and the risk of infection recurrence is provided. A multidisciplinary effort is required to achieve consistent outcomes.